Impacts of high-dose gamma irradiation on the mechanical, structural and thermal properties of doum fiber reinforced High-Density Polyethylene (HDPe) - Mngusuur Scholastica Iorshase; Aliyu Abubakar Sadiq; Lubem James Utume; Emmanuel Ochoyo Adamu; Muhammad Sani; Wasiu Salami Oyeyemi (Recent Advances in Natural Sciences)
High-density polyethylene (HDPe) has widespread application in pharmaceutical packaging and medical devices since it is biocompatible and stable. Research on the impact of high-dose gamma irradiation on structural, thermal, and mechanical properties of Doum fiber-reinforced HDPe composites at 0 wt.%, 20wt.% and 40 wt.% is required due to the composite nature of the material. The research involves synthesis and analysis of gamma irradiation impacts properties of biomass-reinforced HDPe. The samples were irradiated at 0-150 Gy, and then subjected to mechanical testing, thermogravimetric analysis (TGA), and Fourier transforms infrared spectroscopy (FTIR). The findings illustrated that gamma irradiation at 100Gy greatly improved tensile strength, hardness, and impact strength because of enhanced fiber-matrix interaction and crosslinking effects. Tensile strength was improved from 16.93 MPa (0 Gy) to 26.80 MPa, hardness was improved from 53.83 Kgf/mm2 to 70.43 Kgf/mm2, and impact strength was optimum at 1.0187 J/mm. Mechanical properties at 150 Gy were compromised because of degradation of the polymer via chain scission. TGA analysis indicated improved thermal stability at 100Gy, as manifested by the increased onset decomposition temperature, while at 150 Gy, degradation and oxidative effects led to decreased stability. FTIR analysis indicated structural change, in accordance with higher crosslinking at 100Gy and degradation at 150Gy. The results confirm that the modest irradiation (100 Gy) is accountable for optimum mechanical and thermal properties and higher irradiations (150 Gy) cause degradation. It also optimizes the performance of Doum fiber-reinforced HDPe composites to a maximum at 40 wt.% fiber content, and to meet high-performance structural applications in medical, pharmaceutical, and aerospace applications.